2024
DOI: 10.1371/journal.pone.0296790
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal MRI and 1H-MRS study of SCA7 mouse forebrain reveals progressive multiregional atrophy and early brain metabolite changes indicating early neuronal and glial dysfunction

Jean-Baptiste Pérot,
Anna Niewiadomska-Cimicka,
Emmanuel Brouillet
et al.

Abstract: SpinoCerebellar Ataxia type 7 (SCA7) is an inherited disorder caused by CAG triplet repeats encoding polyglutamine expansion in the ATXN7 protein, which is part of the transcriptional coactivator complex SAGA. The mutation primarily causes neurodegeneration in the cerebellum and retina, as well as several forebrain structures. The SCA7140Q/5Q knock-in mouse model recapitulates key disease features, including loss of vision and motor performance. To characterize the temporal progression of brain degeneration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Although the cerebellum is a major target for therapeutic development in ataxias, other brain structures are often affected and must also be considered. Recent magnetic resonance imaging of SCA7 mice revealed progressive atrophy of several forebrain regions, including the striatum and hippocampus [42]. We found that systemic injection of AAV PHP.eB efficiently transduced the striatum and hippocampus and led to a reduction of mATXN7 level (by 56% and 39%, respectively) by shA4 treatment.…”
Section: Efficacy and Limitation Of Aav Phpeb Serotype For Preclinica...mentioning
confidence: 71%
“…Although the cerebellum is a major target for therapeutic development in ataxias, other brain structures are often affected and must also be considered. Recent magnetic resonance imaging of SCA7 mice revealed progressive atrophy of several forebrain regions, including the striatum and hippocampus [42]. We found that systemic injection of AAV PHP.eB efficiently transduced the striatum and hippocampus and led to a reduction of mATXN7 level (by 56% and 39%, respectively) by shA4 treatment.…”
Section: Efficacy and Limitation Of Aav Phpeb Serotype For Preclinica...mentioning
confidence: 71%